Macromedia Flash professional 8 revealed - Shuman, Jim (Thomson Course Technology, 2006)
This title offers step-by-step instructions and in-depth explanations of the features of Macromedia Flash 8. Students will easily master the software as they work through end-of-chapter learning projects and step-by-step tutorials. The full-color interior and user-friendly design create the ideal book for learning the latest features of this popular application